Jaguar (panthera onca) abundance and density in the apff meseta de Cacaxtla, Sinaloa, Mexico - Coronel-Arellano, Helí; Lara-Díaz, Nalleli E.; López-González, Carlos A. (Instituto de Ecología, A.C., 2017)
There is a lack of information about jaguar populations in Sinaloa, Mexico, because there are only anecdotic records and interviews about the presence of this felid. The aim of this study was to generate information about jaguar abundance and density in the Natural Protected Area Meseta de Cacaxtla. To detect jaguar, we used camera traps. The density obtained was 1.59 ind./100 km2 and 15 jaguars for the Natural Protected Area. We considered the Natural Protected Area as an important region for jaguar populations at the Sierra Madre Occidental, because this area may represent a linkage between Sahuaripa and Costa de Jalisco.